The impact of biological age vs. chronological age on the development of the young tennis athlete - Vilela Brito, A. (Coaching and Sport Science Review, 2020)
The aim of this paper is to understand how various factors such as maturation, peak height velocity, body growth and the effect of relative age can interfere with the athlete's development in sports and in personal terms. Studies indicate that athletes` development is made up of several stages of maturation, and it is likely that they may occur at different timings depending on the athlete, their birth date, their upbringing, and the type of practice they have undertaken. Thus, we will have to be aware of the prediction we make of an athlete`s progression because this maturational timing influences both the physical and mental progression of the athlete. This is especially true given that evidence shows that those born in the first semester of the season or year may have early advantages over those born in the second semester. This may include finding ways to limit the ability to give more means and selection to teams or players that are stronger or more mature.